2010
DOI: 10.1111/j.1365-3148.2010.01017.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, serologic and genetic studies of high expressers of the blood group A antigen on platelets*

Abstract: Objective/Aim: The aim of this study is to describe the distribution of the platelet blood group A antigenicity in Euro-Brazilians (EUBs) and Afro-Brazilians (AFBs).Background: A small but significant proportion of individuals express high levels of A or B antigen on their platelets corresponding to the erythrocyte ABO group. The mechanism of increased antigen expression has not been elucidated.Material/Methods: A cohort of 241 blood group A donors was analysed by flow cytometry. Although mean fluorescence int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
3
6
0
Order By: Relevance
“…This procedure allowed us to exclude a prozone phenomenon, or an underestimation of the antigen expression. In accordance with previously published studies [6,7,8,9], we showed that the presence of an A 1 allele had the greatest impact on A-antigen density. An about tenfold increased difference of A antigen expression was discernible between platelets from A 1 and A 2 donors.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…This procedure allowed us to exclude a prozone phenomenon, or an underestimation of the antigen expression. In accordance with previously published studies [6,7,8,9], we showed that the presence of an A 1 allele had the greatest impact on A-antigen density. An about tenfold increased difference of A antigen expression was discernible between platelets from A 1 and A 2 donors.…”
Section: Discussionsupporting
confidence: 81%
“…While it has been established that group A 2 platelets carry considerably less A antigen than those of an A 1 phenotype [3,6,7,9], their differentiation from group O platelets by flow-cytometric analyses were inconclusive. Cooling et al [6] suggested that A 2 platelets possess a Bombay-like phenotype, lacking both A and H antigen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The recipients apparent refractoriness was only associated with the transfusions from the donors with the high expression phenotype; therefore, the authors concluded that donor PLTs with high levels of B antigen, in combination with recipient's ‘high titer' anti-B, were associated with lower than expected post-transfusion PLT increments. Subsequent studies have demonstrated that there are different patterns of A and B antigen high expression on PLTs (that PLTs from group A 2 donors tend to express group O levels of A antigen) and that the frequency of PLT A and B high expression is fairly constant between different populations (2-7%) [33,34,35,36,37,38]. …”
Section: Part 1: Plt Transfusion and Abo Compatibilitymentioning
confidence: 99%